Mix design of porous asphalt mix (PAM) using aggregates of varying strengths for value-add applications - Chiam, Zhi Hui (2018)
The opening of Jurong Rock Caverns produced a large amount of excavated sedimentary rock aggregates which could potentially be used as construction material. The aim of this project is to investigate the feasibility of utilising sedimentary rock and granite aggregates in the construction of low-strength pavement made of porous asphalt mixture. Physical properties of sedimentary rock aggregates were also examined to further determine its characteristics and suitability for asphalt pavements. Three experimental groups (EG1, EG2 AND EG3) with different composition of aggregates were investigated and evaluated. PG 76 binder was used in this study for batching of specimens which has better properties than the conventional PEN 60/70. Prior to the fabrication of specimens, the sedimentary rock aggregates were crushed to size smaller than 19mm and sieved according to the sizes required for the mix. The crushing method adopted aims to optimise the physical properties of the aggregates, especially its flakiness and elongation indices. The experimental groups of different mix were analysed through laboratory tests such as Marshall Stability, Cantabro, Draindown, Moisture Susceptibility and Theoretical Maximum Density Tests to assess the adequacy of the mix for well-fitting applications. Based on the Marshall Stability test, the optimum binder content was found to be 4.5% for EG1, granite control group, and 5.0% for EG3 that contains both granite and sedimentary rock aggregates. EG2 was not further researched on as it does not meet the requirement of 4.0 kN for Marshall Stability value with regards to low-strength pavements. EG3 was found to be of sufficient strength for low-strength pavements from the Marshall Stability Test. However, moisture conditioned specimens from EG3 were not satisfactory for its Marshall Stability value where more researches are needed to further evaluate the feasibility of using sedimentary rocks in porous asphalt.